Physical, Physiological, and Technical Demands in Ultimate Frisbee Small-Sided Games: Influence of Pitch Size - Masanobu Kajiki; Yuto Yamashita; Ryosuke Inada; Takaaki Matsumoto (MDPI AG, 2021)
Small-sided games (SSGs) are common drills used in various team sports, but the exercise intensity in ultimate Frisbee SSG has not yet been investigated. To clarify the physical, physiological, and technical demands of ultimate Frisbee SSG, we investigated the influence of pitch size on exercise intensity during SSG. Nine male college ultimate Frisbee players played (3 vs. 3) SSG on small (SSGS: 30 × 15 m) and large (SSGL: 40 × 20 m) pitches; both SSGs comprised of four 4 min periods, interspersed by 5 min of passive recovery. Players' mean heart rate (170 ± 8 and 171 ± 7 bpm), peak heart rate (184 ± 7 and 184 ± 5 bpm), and blood lactate concentration (11.3 ± 4.7 and 11.8 ± 4.6 mmol/L) were similar in SSGS and SSGL, respectively. The total distance covered (1984 ± 166 m and 1702 ± 80 m) and the distance covered during quick (860 ± 112 m and 696 ± 69 m) and high-intensity running (439 ± 95 and 255 ± 44) in SSGL were significantly longer than those in SSGS (p < 0.05). Conversely, the number of accelerations (45 ± 3 and 41 ± 3) and decelerations (44 ± 3 and 40 ± 4), catching errors (2 ± 1 and 1 ± 1), and turnovers (8 ± 2 and 6 ± 2) in SSGS were significantly greater than those in SSGL (p < 0.05). This study suggests that ultimate Frisbee SSG provides high-intensity training, which stimulates the glycolytic pathway. Furthermore, manipulating SSG pitch size effectively modulates the physical demands of SSG.